If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -2 = 28 + -2 Reorder the terms: -2 + 9x = 28 + -2 Combine like terms: 28 + -2 = 26 -2 + 9x = 26 Solving -2 + 9x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 9x = 26 + 2 Combine like terms: -2 + 2 = 0 0 + 9x = 26 + 2 9x = 26 + 2 Combine like terms: 26 + 2 = 28 9x = 28 Divide each side by '9'. x = 3.111111111 Simplifying x = 3.111111111
| 14(t-6)+4t=6(3t+5)-12 | | -8x+7-0=-56 | | 5z=-3(z+8) | | 3x+9=7x-9 | | -1[a-1(a+-5)]+-3=-5-1(-9+-5) | | 5c=-3(2+8) | | 12(3x+6)-7(2x-6)=2x-26 | | 2(3x-6)=3(x-9) | | 14x-1-5x=-28+12x | | 3x-4(2x+2)=2 | | 8w-10= | | -x+6=-30 | | 5x+12=102 | | 5x=-1.8 | | 6x^2-7=10 | | 7u=4 | | -4x-4=6-3x | | 7x+4=5x+17 | | v-18=3v-7+3 | | a=b-4c | | 4+11s-2=6s+10-3s | | 8y-y=6 | | 8z-48=-16 | | -[a-(a-5)]-3=-5-(-9-5) | | 63=-2x-5x+7 | | 17+b=b-4+7b | | 8+15h-1=8h+79-4h | | 2-3a=4+a | | 4x-17(1-x)=42 | | -8(k-7)-(5+2k)=-11k | | 7x-8=3x+22 | | 2x-a=x-b |